Food insecurity in the vulnerable territory of “Aparecidinha”- Londrina/Paraná: experience of residents - Campos, Eliane Christine Santos de; Antonello , Ideni Terezinha; Cordeiro, Sandra Maria de Almeida; Pires , Patricia Fernanda Ferreira; Silva, Claudia Neves (Technical and Scientific Journal Green Cities, 2025)
This article aims to relate the vulnerabilities expressed in the socio-territorial segregation of residents of the “Aparecidinha” settlement, located in the northern region of Londrina – Pr. and to understand the experience of food insecurity experienced by them with food and nutritional insecurity, based on EBIA (Brazilian Food Insecurity Scale). Qualitative in nature, the research involved bibliographic review, documentary survey and field research.  Understanding food insecurity in vulnerable territories enables the unveiling of realities experienced by people who are invisible because they are on the outskirts of cities, excluded from rights and, often, outside of official statistics. The food and nutritional insecurity experienced by the people who occupy the “Aparicidinha” territory are deeply related to structural poverty, aggravated by the economic crisis that imposes unemployment or underemployment on men and women. The research results will be able to support new studies and contribute to the national debate, as well as the direction of municipal public policies that aim to reduce economic and social inequalities, and that guarantee Human Rights to Adequate Food (DHAA), as foreseen in the Federal Constitution of 1988 and reiterated in the legislation that supports the implementation of the National Food and Nutritional Security Policy.
Keywords: Food Insecurity; Territory.